1988
DOI: 10.1111/j.1467-9310.1988.tb00587.x
|View full text |Cite
|
Sign up to set email alerts
|

The R&D/Production interface in four developed countries

Abstract: The relationship between company R&D and commercial performance, if any, is the subject of much discussion and little measurement. One view (Bisio and Gastwirt 1979) is that meaningful quantitative generalisations on the value of R&D to companies cannot be made. A later study (Bergen 1983) introduced quantitative methods by creating a series of hypotheses. These were tested by scoring related variables and analysing the data for correlations and population differences. The study was confined to one industry to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Relatively few cross‐national studies have been carried out in the area of new product development. The few that have been tend to be based on quite small sample sizes[23,24,25,26,27,28], especially when compared to the many single‐country studies. Nonetheless, the limited results indicate that there are differences in new product practices between countries and there may also be performance differences[3,23,26,28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Relatively few cross‐national studies have been carried out in the area of new product development. The few that have been tend to be based on quite small sample sizes[23,24,25,26,27,28], especially when compared to the many single‐country studies. Nonetheless, the limited results indicate that there are differences in new product practices between countries and there may also be performance differences[3,23,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…Senior management′s involvement and corporate commitment : The impact of these two senior management elements on new product development has been found to be positive[12,35]. Success factors here include: sending clear messages to the entire organization about the role and importance of new product development in the form of broad parameters and a strategic mission for NPD[3,4,27,33,45];ease of access to senior management in case of difficulties or for major decisions[25,27,38];availability of sufficient funds and resources[4,25,31,40,49];the presence of some technical literacy among senior managers [4,23,42];senior management commitment to risk‐taking in product innovation[2,29]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that scientific concepts are western`inventions' and this combined with a lack of individualism blocks creativity in Japan (Dreyfuss, 1987). Bergen et al (1988) identified differences in the R&D productivity of 54 scientific instrument manufacturers in the UK, US, Germany and Japan which were attributed to national culture. Other writers have ascribed R&D productivity to technology (Dumbleton, 1986), organisational factors such as adminis-trative systems and public policy (Tornatzky and Fleischer, 1990) and to the creativity and motivation of scientists (Pelz and Andrews, 1976).…”
Section: National Culture Entrepreneurs and Innovationmentioning
confidence: 99%